Social Media and Political Preferences Among Generation Z in the 2024 Indonesian General Election - Kusumawardani, Vidya; Sheila Silvia Permatasari; Chandra Agustin, Dinar Ayu (Mediakita, 2025)
Social media and politics are inextricably intertwined variables. In a democratic system, social media has proven to be a valuable tool for political engagement. This study investigates the relationship between social media and political preferences among Generation Z in the context of the 2024 Indonesian Presidential Election. A total of 41 undergraduate students from the Faculty of Economics, Business, and Social Sciences at Universitas 17 Agustus 1945 Jakarta participated in an online survey conducted via Google Forms from April to May 2024. The survey targeted students aged 17–22 years from various academic disciplines. The questionnaire was structured into three thematic categories: "Social Media Usage" (5 items), "Social Media and Political Preferences" (15 items), and "Media and Political Preferences" (4 items). The data underwent descriptive quantitative analysis to summarize trends and patterns in the participants’ responses. The results, as presented in Charts 1–22, indicate that Gen Z voters utilize both social and mass media to shape their political views. Approximately 39% relied on social media, while 46% preferred mass media. A primary concern, cited by 78.15% of respondents, centered on the validity of news circulating on social media platforms. Kompas.com emerged as the most trusted source, used by 73.2% to evaluate presidential candidates, 43.9% for parliamentary candidates, and 31.7% to assess the track records of political parties. These findings highlight that, despite being digital natives, Gen Z voters actively evaluate the credibility of political information sources before forming their electoral preferences.